Investigation about the relationship between Mozart's Sonata K448 and the extinction of the fear memory of the environment (Research, Society and Development, 2022)
The memory process is divided into phases. Extinction is the final phase, in which previously established information is suppressed, starting with a new learning process. Objective: To investigate the interference of Mozart's Sonata K448 in the extinction of the memory of fear of the environment. Methods: C57BL/6J mice were used, divided into: G1: Mozart (n=7); G2: Environment (n=7); and G3: Control (n=6). Only the G1 group was exposed to music from intrauterine life onwards. On days 50 to 53 after birth, the animals were subjected to Habituation. On the 54th day, an Aversive Training was performed only with G1 and G2. On the 55th day, the Extinction Test started, lasting twelve consecutive days with the three groups. On the 81st day, all groups passed the Recall Test. The tests were videotaped for analysis. Data were analyzed using the repeated measures ANOVA test, with p≤0.05 being considered significant. Results: There was no groups main effect (F (2;16) =2.46; p=0.118), nor an interaction between days vs. groups (F (4.08;32.62) =1.42; p=0.250). Conclusion: Our results did not show alterations o the extinction memory of animals exposed classical, since the groups´ results were similar over time.